2017
DOI: 10.1002/minf.201700087
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening Approach of Bacterial Peptide Deformylase Inhibitors Results in New Antibiotics

Abstract: The increasing resistance of bacteria to antibacterial therapy poses an enormous health problem, it renders the development of new antibacterial agents with novel mechanism of action an urgent need. Peptide deformylase, a metalloenzyme which catalytically removes N-formyl group from N-terminal methionine of newly synthesized polypeptides, is an important target in antibacterial drug discovery. In this study, we report the structure-based virtual screening of ZINC database in order to discover potential hits as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…The interaction profile of the compounds docked with peptide deformylase showed an excellent fit of epicatechin, ferulic acid, gallic acid, and rosmarinic acid in the binding pocket of the protein, GLN50, GLU133, GLY81, LEU91, GLN65, LEU112, VAL50, and GLY110 (Figure 2). A similar observation was made by Merzoug et al (2017) [103]. Other studies by [104,105] found compounds with hydroxamate functional groups to be viable antibacterial agents when targeting the peptide deformylase protein.…”
Section: Docking Analysissupporting
confidence: 74%
“…The interaction profile of the compounds docked with peptide deformylase showed an excellent fit of epicatechin, ferulic acid, gallic acid, and rosmarinic acid in the binding pocket of the protein, GLN50, GLU133, GLY81, LEU91, GLN65, LEU112, VAL50, and GLY110 (Figure 2). A similar observation was made by Merzoug et al (2017) [103]. Other studies by [104,105] found compounds with hydroxamate functional groups to be viable antibacterial agents when targeting the peptide deformylase protein.…”
Section: Docking Analysissupporting
confidence: 74%
“…Virtual screening like docking and simulation are fast and cheap methods that give sufficient primary information of inhibition pathway of phytochemicals against essential enzymes of various pathogens. 40 Further, in silico structure based drug designing can be used to improve the efficacy of inhibitory effects of Quercetin like natural molecules. This study unbolts the opportunity for further research on these types of natural compounds, as it is evident from the facts that these compounds have great potential to be used as lead molecules in future development of drugs.…”
Section: Resultsmentioning
confidence: 99%
“…In screening for potential antimicrobial agents, most researchers used paper disc diffusion method (Diánez et al, 2018; Kelebek et al, 2017; Merzoug et al, 2018) and broth microdilution method (Romulo et al, 2018; Thielmann et al, 2019; Yousfi et al, 2020). The paper disc diffusion method may be labour consuming and require significant quantities of the test materials.…”
Section: Introductionmentioning
confidence: 99%